Analytical modelling and optimization of a thermal convective microfluidic gyroscope - Vosloo, Surika (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.